Successful production of the potato antimicrobial peptide Snakin-1 in baculovirus-infected insect cells and development of specific antibodies - Almasia, Natalia Ines; Molinari, Maria Paula; Maroniche, Guillermo Andrés; Nahirñak, Vanesa; Barrios Baron, Maria Pilar; Taboga, Oscar Alberto; Vazquez Rovere, Cecilia (2018)
Background: Snakin-1 (StSN1) is a broad-spectrum antimicrobial cysteine-rich peptide isolated from Solanum tuberosum. Its biotechnological potential has been already recognized since it exhibits in vivo antifungal and antibacterial activity. Most attempts to produce StSN1, or homologous peptides, in a soluble native state using bacterial, yeast or synthetic expression systems have presented production bottlenecks such as insolubility, misfolding or low yields. Results: In this work, we successfully expressed a recombinant StSN1 (rSN1) in Spodoptera frugiperda (Sf9) insect cells by optimizing several of the parameters for its expression in the baculovirus expression system. The recombinant peptide lacking its putative signal peptide was soluble and was present in the nuclear fraction of infected Sf9 cells. An optimized purification procedure allowed the production of rSN1 that was used for immunization of mice, which gave rise to polyclonal antibodies that detect the native protein in tissue extracts of both agroinfiltrated plants and stable transgenic lines. Our results demonstrated that this system circumvents all the difficulties associated with recombinant antimicrobial peptides expression in other heterologous systems.